PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN TEMATIK DENGAN TEMA KEGIATAN SEHARI-HARI MELALUI MODEL PEMBELAJARAN INSTANT ASSESMENT DENGAN MEDIA CHOOSE NUMBER DI KELAS III SDN 22 TEPI SELO - NASDAWITA NASDAWITA (JURNAL MANAJEMEN PENDIDIKAN, 2019)
Based on the learning outcomes of Class III students of SDN 22 Tepi Selo on thematic learning with the theme of daily activities it was found that many student learning outcomes in Thematic Learning are incomplete. The purpose of this study is to describe and obtain information about improving student learning outcomes in Thematic Learning with the Theme of Daily Activities through the Model of Instant Learning Assessment with Media Choose Number in Class III SDN 22 Tepi Selo. This research is a classroom action research. Research procedures in this study include planning, action, observation and reflection. This research consisted of two cycles with four meetings. The research subjects consisted of 31 students of Class III SDN 22 Tepi Selo. Research data were collected using a test sheet. Data were analyzed using percentages. Based on the results of research and discussion that has been proposed, it can be concluded that the learning model of the Instant Assessment Learning Model with the media choose number can improve student learning outcomes in Thematic Learning with the Theme of Everyday Activities in Class III SDN 22 Tepi Selo. Student learning outcomes in the first cycle were 72.90 increased to 83.87 with an increase of 10.97%.